A Non-phylogeny-dependent Reassortment Detection Method for Influenza A Viruses - Gong, Xingfei; Hu, Mingda; Wang, Boqian; Yang, Haoyi; Jin, Yuan; Liang, Long; Yue, Junjie; Chen, Wei; Ren, Hongguang (Frontiers in Virology, 2021)
Influenza A virus is a segmented RNA virus whose genome consists of 8 single-stranded negative-sense RNA segments. This unique genetic structure allows viruses to exchange their segments through reassortment when they infect the same host cell. Studying the determination and nature of influenza A virus reassortment is critical to understanding the generation of pandemic strains and the spread of viruses across species. Reassortment detection is the first step in influenza A virus reassortment research. Several methods for automatic detection of reassortment have been proposed, which can be roughly divided into two categories: phylogenetic methods and distance methods. In this article, we proposed a reassortment detection method that does not require multiple sequence alignment and phylogenetic analysis. We extracted the codon features from the segment sequence and expressed the sequence as a feature vector, and then used the clustering method of self-organizing map to cluster the sequence for each segment. Based on the clustering results and the epidemiological information of the virus, the reassortment detection was implemented. We used this method to perform reassortment detection on the collected 7075 strains from Asia and identified 516 reassortment events. We also conducted a statistical analysis of the identified reassortment events and found conclusions consistent with previous studies. Our method will provide new insights for automating reassortment detection tasks and understanding the reassortment patterns of influenza A viruses.